Thermal, Electrical and Microstructural Characterization of Sno2-Based Ceramic Composites - Mas’ut, Aiza Masyati (2008)

(untitled)
In this work, the photoflash and two-probe technique were used to measure thermal diffusivity and electrical conductivity, respectively, on tin (IV) oxide-based gas sensor materials i.e. SnO2/CuO and SnO2/ZnO samples. All measurements were made at room temperature. It was found that the thermal diffusivity value of pure SnO2 was 1.45 × 10-2 cm2s-1. The thermal diffusivity of SnO2/CuO ceramic composites with addition of up to 30 mole% CuO increases to 7.50 × 10-2 cm2s-1 but further additions of CuO decrease the thermal diffusivity value to 6.21 × 10-2 cm2s-1. For SnO2/ZnO ceramic composites, the thermal diffusivity is in the range of 1.01 to 2.62 × 10-2 cm2s-1. Changes of the grain size or changes of the porosity volume have been suggested to be responsible for the variation in the thermal diffusivity behavior and this was supported by SEM micrographs. The electrical resistivity of pure SnO2 was found to be 2.11 × 101 Ωcm. Both SnO2/CuO and SnO2/ZnO ceramic composites indicated that their electrical resistivity values were in the range of 4.067 × 105 Ωcm to 8.667 × 106 Ωcm and 2.739 × 105 Ωcm to 5.650 × 106 Ωcm, respectively. Their electrical resistivity trends were actually decrease with increasing additions of either CuO or ZnO. The variation in the electrical resistivity of these samples has been explained based on the changes of free electron concentration.